Komunikasi Partisipatif Kelompok Sadar Wisata (Pokdarwis) Terkait Program Ekowisata di Kelurahan Bontang Baru Kota Bontang - Firdausi, Hilda Annisa Nur; Juwita, Rina; Boer, Kheyene Molekandella (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
In realizing the concept of good governance, community participation is needed to participate in development. In this regard, the government formed Pokdarwis as a development agent in the context of tourism as a tool for developing public awareness of the environment around them. This study uses Development Communication as the Grand Theory, Participatory Communication as the Middle Theory, and the service concept that uses four indicators of participatory communication namely, Heteroglasia, Dialogic, Polyphony, and Carnival. This research with the theme of ecotourism uses a type of qualitative description with a purposive sampling technique with the selection of informants based on certain criteria. Based on the findings in the field, it was found that some of the four concepts were found in the Pokdarwis participatory communication practices but some were not found meaning they did not meet the criteria to be included in the four indicators.